Dampak Implementasi Platform Merdeka Mengajar Bagi Guru di Sekolah Penggerak: Studi Kasus di SDN 4 Gulang - Ririk Woro Hapsari; Matsuri Matsuri; Supianto Supianto (Jayapangus Press, 2026)
The Merdeka Curriculum is a new educational framework introduced by the Indonesian government to improve national education quality and support learning recovery after the Covid-19 pandemic. Its transition from the 2013 Curriculum requires teachers to adapt and relearn the curriculum, which has challenged many educators. To support this process, the government launched the Merdeka Mengajar Platform (PMM) as a self-directed learning tool for teachers. This study aims to examine in depth the impact of PMM on teachers in a Sekolah Penggerak (driving school) at the elementary level. A qualitative descriptive design with a case study approach was employed at SDN 4 Gulang, Mejobo District, Kudus Regency. Data were collected through interviews, observation, and document analysis, and their credibility was ensured through source and technique triangulation, followed by data reduction, data display, and conclusion drawing. The findings reveal three interrelated impacts. First, PMM improved teachers' digital literacy, shown by their growing ability to operate the platform, complete training topics, and design teaching materials using Microsoft Word and Canva. Second, PMM fostered learning innovation, enabling teachers to move from monotonous, teacher-centred instruction toward more active, creative, and enjoyable learning that raised students' engagement. Third, PMM supported teachers' professional development through its community feature, webinars, and certified training integrated with performance management. The study concludes that the Merdeka Mengajar Platform exerts a positive and mutually reinforcing impact on elementary teachers in a Sekolah Penggerak, where improved digital literacy underpins both learning innovation and continuous professional growth.